EFEKTIVITAS PENGGUNAAN GOOGLE SITES DALAM PEMBELAJARAN MENULIS PUISI SISWA KELAS XI SMA MUHAMMADIYAH 1 UNISMUH MAKASSAR - Nur Hidayah; M Akhir; Wahyu Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to prove the effectiveness of using Google Sites in teaching poetry writing to class XI students at SMA Muhammadiyah 1 Unismuh Makassar. This research uses a quantitative approach with an experimental method, specifically a pretest-posttest control group design. The data collection techniques used were written tests in the form of multiple choice and essays. The results showed that the average pretest score of the experimental class was 67.33 and posttest was 80.20, while the control class had an average pretest of 64.33 and posttest of 72.42. These results indicate a significant difference in learning outcomes, suggesting that Google Sites is effective in improving students' poetry writing skills.